Fabrication and plasma modification of polymer scaffolds for regenerative and replacement medicine - Vasilets, Victor N.; Surguchenko, Valentina A.; Sevastianov, Viktor I. (International Conference on Plasma Surface Engineering, 2013)
Materials that serve as analogues for the native extra-cellular matrix (ECM) can be used in medicine to aid in either the reconstruction or regeneration of damaged tissue and organs. Polymer matrices have been used for regeneration of bone, liver, pancreas, skin and other tissues. Macroporous. biodegradable polymer scaffolds have been prepared by numerous techniques including solvent casting/salt leaching, phase separation, solvent evaporation, and fiber bonding to form a polymer mesh. The main goal of this research was to apply novel physical processing techniques to fabricate and modify highly porous implantable biodegradable scaffolds. More specifically, this involves fabricating scaffolds using electrospinning, piezoelectric printing, gel sublimation techniques and finally modification of matrixes by plasma treatment in order to control chemical structure and morphology of scaffolds.